1984
DOI: 10.1093/geronj/39.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Norepinephrine in Normal Young and Aged Men: Relationship with Sleep

Abstract: This study explored the relationship between age-related elevations of plasma norepinephrine (NE) levels (thought to reflect heightened sympathetic nervous system activity) and sleep. Plasma NE levels were consistently and significantly greater in 8 aged than 10 young men across a 24-hr study period. For both groups, plasma catecholamine levels remained stable near bedtimes and rise times and during spontaneous and experimentally induced nighttime awakenings; reversal of the sleep/wake pattern (nighttime wakef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…While some studies have demonstrated that an increased catecholamine level due to a medical disorder is accompanied by impaired sleep patterns, so far neither experimentally induced short nighttime awakenings nor selective REM sleep withdrawal have been shown to elevate plasma catecholamine levels [32,33]. In the study by Prinz et al [33], only very mild fragmentation procedures were applied compared to other fragmentation procedures [20,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have demonstrated that an increased catecholamine level due to a medical disorder is accompanied by impaired sleep patterns, so far neither experimentally induced short nighttime awakenings nor selective REM sleep withdrawal have been shown to elevate plasma catecholamine levels [32,33]. In the study by Prinz et al [33], only very mild fragmentation procedures were applied compared to other fragmentation procedures [20,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Prinz et al [33], only very mild fragmentation procedures were applied compared to other fragmentation procedures [20,34,35]. In the study by Nishihara and Mori [32], only urinary catecholamines were determined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans report that sleep onset is associated with reduced plasma EPI [131,132] and no change [131] or decreased plasma NE levels [132] . From early studies it is not clear whether reduced plasma catecholamines correlate with circadian-or sleep-dependent processes, because sleep was not monitored [127,129,133] . Less data are available regarding changes in catecholamines during the different sleep stages.…”
Section: Sns and Sleepmentioning
confidence: 99%
“…Downloaded from https://academic.oup.com/biomedgerontology/article-abstract/55/3/M155/2947958 by guest on 08 June 2019 in later life. Increased SNS activity has been linked to cognitive impairment and to sleep disturbances in normal older persons (29,30). Increased SNS activity has also been associated with some forms of hypertension (31), with the progression of congestive heart failure (32,33), and with potentially fatal postmyocardial infarction events such as ventricular cardiac arrhythmia (34).…”
Section: Discussionmentioning
confidence: 99%